Ultrastructural nonisotopic mapping of nucleolar transcription sites in onion protoplasts - Melcák, I; Risueño, M C; Raska, I (Journal of structural biology, 1996)
The post- and preembedding ultrastructural localization of transcribing rRNA genes has been carried out in nucleoli of permeabilized onion growing root tip protoplasts by means of the nonisotopic bromouridine method. By means of both post- and preembedding approaches, major synthetic sites were identified with morphologically distinct subdomains of dense fibrillar components, with some signal also being associated with nucleolar fibrillar centers and vacuoles. Moreover, labeled medusoid fibrils within distinct domains seen in Lowicryl thin sections likely represent the morphological correlate of transcribing nucleolar genes.
Keywords: Protoplasts; protoplasty; fluorescenční mikroskopie; Vacuoles; Microscopy, Fluorescence; Tissue Embedding; buněčné jadérko; Plant Roots; zalévání tkání; uridin; RNA, Plant; Transcription, Genetic; genetická transkripce; kořeny rostlin; barvení a značení; Staining and Labeling; Uridine; Bromouracil; Microscopy, Immunoelectron; vakuoly; bromouracil; Cell Nucleolus; Allium; imunoelektronová mikroskopie; RNA ribozomální; RNA, Ribosomal; RNA rostlin